Survival benefit of liver resection for Barcelona Clinic Liver Cancer stage B hepatocellular carcinoma. Issue 8 (8th May 2017) - Kim, H; Ahn, S W; Hong, S K; Yoon, K C; Kim, H-S; Choi, Y R; Lee, H W; Yi, N-J; Lee, K-W; Suh, K-S
Abstract: Background: Although transarterial chemoembolization is recommended as the standard treatment for Barcelona Clinic Liver Cancer stage B hepatocellular carcinoma (BCLC-B HCC), other treatments including liver resection have been used. This study aimed to determine the survival benefit of treatment strategies including resection for BCLC-B HCC compared with non-surgical treatments. Methods: The nationwide multicentre database of the Korean Liver Cancer Association was reviewed. Patients with BCLC-B HCC who underwent liver resection as a first or second treatment within 2 years of diagnosis and patients who received non-surgical treatment were selected randomly. Survival outcomes of propensity score-matched groups were compared. Results: Among 887 randomly selected patients with BCLC-B HCC, 83 underwent liver resection as first or second treatment and 597 had non-surgical treatment. After propensity score matching, the two groups were well balanced (80 patients in each group). Overall median survival in the resection group was better than that for patients receiving non-surgical treatment (50·9 versus 22·1 months respectively; P < 0·001). The 1-, 2-, 3- and 5-year overall survival rates in the resection group were 90, 88, 75 and 63 per cent, compared with 79, 48, 35 and 22 per cent in the no-surgery group ( P < 0·001). In multivariable analysis, non-surgical treatment only (hazard ratio (HR) 3·35, 95 per cent c.i. 2·16 to 5·19; P < 0·001), albumin level below 3·5 g/dl (HR 1·96, 1·22 to 3·15; P = 0·005) and largest tumour size greater than 5·0 cm (HR 1·81, 1·20 to 2·75; P = 0·005) were independent predictors of worse overall survival. Conclusion: Treatment strategies that include liver resection offer a survival benefit compared with non-surgical treatments for potentially resectable BCLC-B HCC. Abstract : Selected patients benefit